Keanekaragaman Jenis Ikan Hasil Tangkapan Nelayan Di Kelurahan Tanjung Solok Tanjung Jabung Timur - Nia Katarina, Happy; Dwi Kartika , Winda; Wulandari, Tia (Universitas Jambi, 2019)
This study was conducted in Tanjung Solok subdistrict, Kuala Jambi, Tanjung Jabung Timur from August to September 2017. The aim of this study to knowing the diversity of fish that caught by fisherman and sold in Tanjung Solok fish bangsal. Samples were collected from 4 bangsal and were identified based on morphological characteristics. The number of samples in this study consisted of 11 order, 23 family and 32 species. The highest number of species from order Perciformes in the following quantities 10 family and 15 species were identified. There were different of species number that founded in each bangsal (28 species in bangsal I, 23 species in bangsal II, 24 species in bangsal III and 25 species in bangsal IV). 17 species of fish can be found in all of bangsal. Type of fish catcher that most often used in Tanjung Solok Subdistrict are Gill net and Rawai.